Saponins in Chinese Herbal Medicine Exerts Protection in Myocardial Ischemia–Reperfusion Injury: Possible Mechanism and Target Analysis - Wang, Ruiying; Wang, Min; Zhou, Jiahui; Wu, Daoshun; Ye, Jingxue; Sun, Guibo; Sun, Xiaobo (Frontiers in Pharmacology, 2021)
Myocardial ischemia is a high-risk disease among middle-aged and senior individuals. After thrombolytic therapy, heart tissue can potentially suffer further damage, which is called myocardial ischemia-reperfusion injury (MIRI). At present, the treatment methods and drugs for MIRI are scarce and cannot meet the current clinical needs. The mechanism of MIRI involves the interaction of multiple factors, and the current research hotspots mainly include oxidative stress, inflammation, calcium overload, energy metabolism disorders, pyroptosis, and ferroptosis. Traditional Chinese medicine (TCM) has multiple targets and few toxic side effects; clinical preparations containing Panax ginseng C. A. Mey., Panax notoginseng (Burk.) F. H. Chen, Aralia chinensis L., cardioprotection, and other Chinese herbal medicines have been used to treat patients with coronary heart disease, angina pectoris, and other cardiovascular diseases. Studies have shown that saponins are the main active substances in TCMs containing Panax ginseng C. A. Mey., Panax notoginseng (Burk.) F. H. Chen, Aralia chinensis L., and Radix Astragali. In the present review, we sorted the saponin components with anti-MIRI effects and their regulatory mechanisms. Each saponin can play a cardioprotective role via multiple mechanisms, and the signaling pathways involved in different saponins are not the same. We found that more active saponins in Panax ginseng C. A. Mey. are mainly dammar-type structures and have a strong regulatory effect on energy metabolism. The highly active saponin components of Aralia chinensis L. are oleanolic acid structures, which have significant regulatory effects on calcium homeostasis. Therefore, saponins in Chinese herbal medicine provide a broad application prospect for the development of highly effective and low-toxicity anti-MIRI drugs.